Impact of Decitabine Conditioning on Allo‐HSCT Outcomes in AML and Intermediate‐to‐High‐Risk MDS Patients in Remission - Shuling Yu; Wanchuan Zhuang; Shengfa Gao; Tongyu Li; Xiao Yan; Guifang Ouyang; Ping Zhang (Cancer Medicine)
ABSTRACT Background Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) remains the sole curative option for myeloid malignancies, though high toxicity from conditioning regimens and complications like graft‐versus‐host disease (GVHD) limit its success. The potential benefit of incorporating decitabine (DAC) into conditioning regimens for acute myeloid leukemia (AML) and intermediate‐to‐high‐risk myelodysplastic syndromes (MDS) patients in remission remains unclear. Methods We conducted a retrospective, single‐center study analyzing data from January 2016 to December 2020 at the First Affiliated Hospital of Ningbo University with a median follow‐up of 45.05 months (range, 1–96 months). Outcomes were compared between patients receiving DAC+HSCT versus HSCT alone, with primary endpoints of 5‐year overall survival (OS), progression‐free survival (PFS), and relapse rate. Secondary analyses examined outcomes by remission status (CR1 vs. others) and age subgroups (< 31.5 years). Immune cell subsets (CD3−CD56+ NK cells) were evaluated for GVHD correlation. Results The DAC+HSCT group exhibited 5‐year OS of 51.9% and PFS of 46.1%, compared to 67% OS and 56.5% PFS in the HSCT‐only group. The 5‐year relapse rate was 16.9% for DAC+HSCT versus 23.2% for HSCT alone. DAC did not significantly improve outcomes in complete remission (CR1) patients but improved OS and PFS in patients under 31.5 years of age. Elevated CD3−CD56+ NK cells in the DAC+HSCT group were associated with higher incidence of severe acute GVHD (aGVHD). Conclusion While DAC conditioning did not provide overall survival benefit for AML/MDS patients undergoing allo‐HSCT, it improved outcomes in younger individuals (< 31.5 years). Higher NK cell proportions may serve as a potential biomarker for early aGVHD intervention, warranting further investigation into risk‐stratified conditioning approaches.